Poverty and SMEs: A New Pradigm of SDGs Development - Lukman Hakim; Aulia Hapsari Juwita; Selfia Bintariningtyas; Danur Condro Guritno (Universitas Ahmad Dahlan, 2021)
Poverty alleviation and micro-small enterprises are the essential topics in discussing the paradigm of Sustainable Development Goals (SDGs). Micro and small businesses are considered as a panacea to alleviate poverty. So the relationship between poverty and the existence of micro and small enterprises is theoretically unidirectional. In other words, if poverty increases, micro, and small enterprises will also increase. To see the effect of poverty on micro and small businesses, this study will use the Village Potential Data (Podes) 2018 with a total of 8559 villages/wards in Central Java Province. Apart from poverty, this study will also examine the effect of technology as represented by the number of electricity customers, health from the number of supporting health centers, and finally education represented by the number of Public Elementary Schools (SDN), State Junior High Schools (SMPN) and State Senior High Schools (SMAN). By using multiple regression models, an interesting relationship is found. Those that have a unidirectional relationship to micro and small enterprises are poverty, technology, health, and primary education (SDN). The role of education in the growth of micro and small businesses strengthens Duflo's thesis (2001) on the effect of education on reducing unemployment which earned him the Nobel Prize in 2019. Meanwhile, junior and secondary education for its effect on micro and small enterprises is negative. This showed that the impact of secondary education is that it provides the possibility to work in other sectors outside of micro and small enterprises